Antioxidant Content of Tisane of Cocoa Bean Shells as Affected by Roasting Temperatures - ., Gumelar; Firmanto, Hendy; Nurcholis, Mochamad (Indonesian Coffee and Cocoa Research Institute, 2022)
Cocoa bean shell is a by-product of processing chocolate products that can be used as a tea infusion because it contains bioactive compounds such as polyphenols which act as antioxidants. Roasting plays a very important role in the development of aromas and flavors. The temperature commonly used in roasting is about 100 – 150 ºC. Phenolic content plays a role in the formation of sensory properties of the product due to the presence of interaction with proteins through the Maillard reaction that occurs in the roasting process. This study aims to determine the effect of roasting temperature on the antioxidant activity of tea infusions from cocoa bean shells. The methods used in this study are the folin-ciocalteu method and the DPPH method. Cocoa bean shell tea with a roasting temperature of 100ºC, 20 minutes has the highest total phenols, antioxidant levels, and radical scavenging activity of 21.54 ± 0.37 mg GAE/g; 12.80 ± 0.17 mg AA/g; and 85.18 ± 1.28%. The total amount of phenols has a very strong correlation to antioxidant levels, radical scavenging, the color value of the brew L*, b*, and is inversely proportional to the color value of a*. Cocoa bean shell tea roasting temperature of 140ºC, 18 minutes has the highest IC50 value of 22.76 mg /ml. In addition, the roasting temperature can affect the sensory attribute character of cocoa bean shell tea.